Enhancing Arabic Vocabulary Mastery through Digital Literacy: Overcoming Challenges and Implementing Effective Strategies - Subkhi, Muhammad; Haning Tyas, Divara Aulia (WISE Pendidikan Indonesia, 2024)
This study explores the implementation of digital literacy-based learning strategies in Arabic vocabulary (mufrodat) education, aiming to enhance students' comprehension and proficiency. Despite its potential, several challenges impede effective application, including limited access to technology and infrastructure, inadequate digital literacy skills, insufficient authentic assessment methods, and lack of support and guidance from educators. To address these challenges, this study recommends improving technological access and infrastructure, enhancing digital literacy skills through targeted training and workshops, developing authentic assessment methods, and providing comprehensive support and guidance for teachers. The implementation of these solutions necessitates collaboration among government bodies, educational institutions, teachers, and students. This research significantly contributes to the field of Arabic language education by integrating digital literacy, thereby enhancing the overall quality of education. The findings provide valuable insights for educators in designing effective learning strategies, for policymakers in formulating supportive educational policies, and for researchers in conducting further studies on digital literacy and Arabic language learning. The study underscores the importance of digital literacy in modern education and its role in fostering improved learning outcomes.